DEVELOPMENT AND USABILITY EVALUATION OF AN ANDROID-BASED 3D VIRTUAL CAMPUS TOUR USING THE PROTOTYPE MODEL - Rachman, Andy; Nugroho, Hendro; Saputra, Fitra Kurnia; Sulistyowati, Sulistyowati; Kristiana, Wiwin Agus; Septianto, Tri (LPPM Universitas Jambi, 2026)
The rapid development of digital technology has encouraged universities to adopt innovative media for campus promotion and information delivery. Conversely, numerous extant virtual campus tour applications are constrained by static visualizations and a dearth of interactivity, thereby impeding user engagement and spatial comprehension of campus settings. This research endeavors to design and assess an Android-based 3D virtual campus tour application, facilitating user exploration of campus facilities within an immersive and interactive digital framework. The system was constructed utilizing the prototype model and executed with the Unity game engine to facilitate real-time 3D visualization and user interaction. The application's performance was evaluated using Black Box Testing, the System Usability Scale (SUS), and the ISO 9126 software quality model. The usability assessment encompassed 22 participants, whereas the software quality evaluation involved 100 respondents, comprising both university students and prospective students. The results showed that the application received a System Usability Scale (SUS) score of 71.9, indicating a good level of usability. Moreover, the ISO 9126 analysis shows that the system meets acceptable standards for functionality (79.7%), usability (81%), and efficiency (79.3%). The results show that the suggested application offers a useful and engaging digital platform for introducing campus environments. This study contributes a mobile-based 3D virtual campus application evaluated through Black Box Testing, SUS, and ISO 9126, with potential use as a digital promotion and campus orientation tool for higher education institutions.